Wheat PR‐1 proteins are targeted by necrotrophic pathogen effector proteins. (10th August 2016) - Breen, Susan; Williams, Simon J.; Winterberg, Britta; Kobe, Bostjan; Solomon, Peter S.
Summary: Recent studies have identified that proteinaceous effectors secreted by Parastagonospora nodorum are required to cause disease on wheat. These effectors interact in a gene‐for‐gene manner with host‐dominant susceptibilty loci, resulting in disease. However, whilst the requirement of these effectors for infection is clear, their mechanisms of action remain poorly understood. A yeast‐two‐hybrid library approach was used to search for wheat proteins that interacted with the necrotrophic effector SnTox3. Using this strategy we indentified an interaction between SnTox3 and the wheat pathogenicity‐related protein TaPR‐1‐1, and confirmed it by in‐planta co‐immunprecipitation. PR‐1 proteins represent a large family (23 in wheat) of proteins that are upregulated early in the defence response; however, their function remains ellusive. Interestingly, the P. nodorum effector SnToxA has recently been shown to interact specifically with TaPR‐1‐5. Our analysis of the SnTox3–TaPR‐1 interaction demonstrated that SnTox3 can interact with a broader range of TaPR‐1 proteins. Based on these data we utilised homology modeling to predict, and validate, regions on TaPR‐1 proteins that are likely to be involved in the SnTox3 interaction. Precipitating from this work, we identified that a PR‐1‐derived defence signalling peptide from the C‐terminus of TaPR‐1‐1, known as CAPE1, enhanced the infection of wheat by P. nodorum in an SnTox3‐dependent manner, but played no role in ToxA‐mediated disease. Collectively, our data suggest that P. nodorum has evolved unique effectors that target a common host‐protein involved in host defence, albeit with different mechanisms and potentially outcomes. Significance Statement: The mechanisms or modes‐of‐action of necrotrophic effector proteins in facilitating plant diseases are largely unknown. This report provides evidence that these critical pathogen proteins interact with the important, yet poorly understood, wheat PR‐1 proteins. The discovery that two independent pathogen effector proteins both target PR‐1 proteins strongly implicates a role for this protein interaction in facilitating disease.